Model for Determining Earth's Gravitational Acceleration on a Mathematical Pendulum - Azahra, Astrid Sulistya; Yuningsih, Siti Hadiaty; Kalfin, Kalfin (International Journal of Quantitative Research and Modeling, 2024)
Gravity is an accelerating property of the earth that causes objects to fall freely. The acceleration of gravity is not the same at every place on the Earth's surface. To measure the Earth's gravity (small g), scientists can use various techniques, such as dropping a mass from a certain height and measuring the time it takes to fall to the ground or using a mathematical pendulum to measure the period of oscillation and use it to calculate the acceleration due to gravity. In this paper, a study of the mathematical pendulum in the measurement of the Earth's gravitational acceleration is conducted, and the measurement experiment is illustrated. Method To measure the length of the pendulum, you must have a ruler, meter stick, or tape measure. At the top end of the string, start the measurement at the point where the string rotates out of place. Then, measure up to the center of the pendulum, which is the object hanging on the string. From the results of this study, it can be concluded that the value of the period of a pendulum is affected by several factors, including the length of the rope used and the angle of initial deviation, while the factors that do not affect the period are the mass and diameter of the pendulum.